Authentication Techniques in Wireless Sensor Networks : A Survey - R. Jensi, M. Mary Madura Selvam, (International Journal of Scientific Research and Management (IJSRM), 2015)
A wireless Sensor Network (WSN) consists of a large number of sensor nodes mostly deployed in places where monitoring thenodes is highly tougher. The most commonly used authentication techniques are public key cryptography or private keycryptography. In some networks a node will be selected as cluster head which will be communicating with the base stationthrough a trusted server, In such cases the nodes has to be authenticated to ensure the security. Authentication ensures the nodalsecurity in a network. In sensor networks, confidentiality, integrity, authenticity, non repudiation and compromise node are mainfeatures to take care off. In this paper, the various authentication techniques in Wireless Sensor Networks and its methodologiesare discussed.